2016
DOI: 10.1515/ngoe-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ICTs on Innovation Activities: Indication for selected European countries

Abstract: The development and usage of information and communication technologies (ICTs) has particularly increased in the last two decades, while at the same time showing great potential to improve the efficacy of business processes, facilitate and drive innovations, and therefore increase competitiveness. Innovation activities represent an important factor for social and economic change as well as for increasing competitive advantages at both the national and firm levels. This paper focuses on the role that ICTs play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
10
0
3
Order By: Relevance
“…Also, they showed that innovation and the use of ICTs substantially impact the performance of the businesses studied. After a panel regression analysis, the results obtained by Zoroja (2016) confirmed the impact of ICTs as a supporting factor for innovation activities.…”
Section: Resultsmentioning
confidence: 65%
“…Also, they showed that innovation and the use of ICTs substantially impact the performance of the businesses studied. After a panel regression analysis, the results obtained by Zoroja (2016) confirmed the impact of ICTs as a supporting factor for innovation activities.…”
Section: Resultsmentioning
confidence: 65%
“…SMEs will have good competitiveness if they have adopted IT in carrying out their business activities (Apulu & Latham, 2010). While (Zoroja, 2016), also has a similar opinion that SMEs who have IT will be more innovative to be able to compete with other MUs. Information technology will have a positive impact on the company (N. A. .…”
Section: Literature Reviewmentioning
confidence: 99%
“…ICTs in business determine technological progress but also determine the existence of a variety of innovation potentials with positive effects on enterprises performance (Cuevas-Vargas, Estrada, and Larios-Gómez, 2016;Zoroja, 2016). For example, the use of ICTs enables firms to restructure their organizations (flattening of hierarchies and delegating responsibilities), to re-engineer business processes (like introducing just-in-time management or engaging in E-commerce) and to develop completely new products (e.g.…”
Section: Enterprises Selling Onlinementioning
confidence: 99%